Investors and Markets : Portfolio Choices, Asset Prices, and Investment Advice. - Sharpe, William F. (Princeton lectures in finance., 2010)
In Investors and Markets, Nobel Prize-winning financial economist William Sharpe shows that investment professionals cannot make good portfolio choices unless they understand the determinants of asset prices. But until now asset-price analysis has largely been inaccessible to everyone except PhDs in financial economics. In this book, Sharpe changes that by setting out his state-of-the-art approach to asset pricing in a nonmathematical form that will be comprehensible to a broad range of investment professionals, including investment advisors, money managers, and financial analysts. Bridging th.